2015
DOI: 10.1371/journal.pone.0136093
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulating Cathepsin K in Patients with Chronic Heart Failure

Abstract: Cysteinyl cathepsin K (CatK) is one of the most potent mammalian collagenases involved in cardiovascular disease. Here, we investigated the clinical predictive value of serum CatK levels in patients with chronic heart failure (CHF). We examined 134 patients with CHF, measuring their serum CatK, troponin I, high-sensitive C-reactive protein, and pre-operative N-terminal pro-brain natriuretic peptide levels. The patients were divided into two groups: the 44 patients who showed a left ventricular (LV) ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Cathepsin family members such as CatK and CatS have been shown to play a critical role in metabolic and inflammatory cardiovascular disorders . Several clinical studies reported that there is relationship between plasma CatK levels and cardiovascular disease stages and progression . Our research and studies by other groups have demonstrated the increased expression and activity of CatK in cardiovascular tissues in response to various injuries .…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Cathepsin family members such as CatK and CatS have been shown to play a critical role in metabolic and inflammatory cardiovascular disorders . Several clinical studies reported that there is relationship between plasma CatK levels and cardiovascular disease stages and progression . Our research and studies by other groups have demonstrated the increased expression and activity of CatK in cardiovascular tissues in response to various injuries .…”
Section: Discussionsupporting
confidence: 59%
“…Initially, cathepsins were recognized to function as scavengers for protein recycling in lysosomes and endosomes of mammalian cells under physiological and pathological conditions . However, the recognition of the cysteinyl cathepsins led to the exploration of their functions in metabolic and inflammatory cardiovascular disorders . Like the members of the MMP family, most of the cathepsins have been shown to be regulatory exoproteases that are widely expressed in various tissues or cells by inflammatory cytokines and growth factors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cathepsins were found to play a role in regulating many key physiological processes, such as generating epitopes for antigen presentation within the immune system (Sadegh-Nasseri and Kim 2015). Cathepsins have garnered a great deal of interest for their apparent role in many disease states, including cardiovascular-related diseases (Platt and Shockey 2015; Zhao et al 2015), neurodegenerative diseases (Chandra et al 2015; Bae et al 2015), cancer (Gomez-Auli et al 2015; Loser and Pietzsch 2015), and chronic lung disease (Lecaille et al 2016). Turk et al (2012) best described cathepsin activity in living organisms as “a delicate balance of expression, targeting, zymogen activation, inhibition by protein inhibitors, and degradation.” Cathepsins B, H, L, C, and X are postulated to be ubiquitously expressed in human tissues as part of normal protein recycling pathways (Turk et al 2012).…”
Section: Cathepsinsmentioning
confidence: 99%
“…The expression of cathepsin K is obviously higher in the myocardial tissue of patients with heart failure, dilated and hypertrophic cardiomyopathy 14,15 . The expression of cathepsin K is closely related to the development of chronic heart failure, and cathepsin K can be used as a biomarker of cardiac remodeling and dysfunction 16 . ODN is a selective and reversible inhibitor of cathepsin K. A large number of clinical and experimental studies have found that ODN treatment for osteoporosis has obvious effects 17 .…”
Section: Introductionmentioning
confidence: 99%